Heat Shock Proteins 90 kDa: Immunomodulators and Adjuvants in Vaccine Design Against Infectious Diseases - Corigliano, Mariana G.; Sander, Valeria A.; Sánchez López, Edwin F.; Ramos Duarte, Víctor A.; Mendoza Morales, Luisa F.; Angel, Sergio O.; Clemente, Marina (Frontiers in Bioengineering and Biotechnology, 2021)
Heat shock proteins 90 kDa (Hsp90s) were originally identified as stress-responsive proteins and described to participate in several homeostatic processes. Additionally, extracellular Hsp90s have the ability to bind to surface receptors and activate cellular functions related to immune response (cytokine secretion, cell maturation, and antigen presentation), making them very attractive to be studied as immunomodulators. In this context, Hsp90s are proposed as new adjuvants in the design of novel vaccine formulations that require the induction of a cell-mediated immune response to prevent infectious diseases. In this review, we summarized the mechanisms by which Hsp90s activate and modulate professional antigen-presenting cells, and we also discuss the adjuvant properties of Hsp90s when they are either alone or complexed, fused to or linked to a peptide to add light to the knowledge of Hsp90s as carriers and adjuvants in the design of vaccines against infectious diseases.